Recurrent Silent Thyroiditis as a Sequela of Postpartum Thyroiditis - Preaw Hanseree; Vincent Bryan Salvador; Issac Sachmechi; Paul Kim (Case Reports in Endocrinology)
Thyroiditis encompasses a group of disorders characterized by thyroid inflammation. Though clinically indistinguishable from silent thyroiditis, postpartum thyroiditis occurs in women within 12 months after delivery. Recurrent postpartum thyroiditis in subsequent pregnancies is common, but recurrent silent thyroiditis is rare. We reported a case of patient with recurrent episodes of thyroiditis, unrelated to pregnancy, after an episode of postpartum thyroiditis. It is of interest that postpartum thyroiditis and silent thyroiditis could occur closely to each other; however, the link between these disorders is not well established. This report is to remind physicians of the possibility of recurrent silent thyroiditis in women with a history of postpartum thyroiditis.